Non-state regulatory regimes understanding institutional transformation - Senn, Myriam (Springer, 2011)
Non-State Regulatory Regimes explores how the concept of regulation continues to evolve. The focus is placed on those forms of regulation that are different from state regulation or present alternatives to state regulation. Departing from an analysis of the goals and policies of the traditional regulatory state, the emergence of ?regulation by other means? is examined. The approach is interdisciplinary encompassing various perspectives be they legal, political, international relations-based, economic, or sociological. The task of comprehending non-state regulation is a daunting one. To date, a number of essays already exist, which concentrate on specific aspects of the issue. In comparison to these essays, this study is innovative in that it applies a holistic view. Linking public policy approaches to regulation, it draws a theoretical path to understanding the emergence and persistence of non-state jurisdictional assertions and regulatory regimes.